Backreaction from inhomogeneous matter fields during large-scale structure formation - Flörchinger, Stefan; Tetradis, Nikolaos; Wiedemann, Urs Achim (Physical review, 2021)
We study how inhomogeneities of the cosmological fluid fields backreact on the homogeneous part of energy density and how they modify the Friedmann equations. In general, backreaction requires to go beyond the pressureless ideal fluid approximation, and this can lead to a reduced growth of cosmological large-scale structure. Since observational evidence favors evolution close to the standard growing mode in the linear regime, we focus on two-component fluids in which the nonideal fluid is gravitationally coupled to cold dark matter and in which a standard growing mode persists. This is realized, e.g., for a baryonic fluid coupled to cold dark matter. We calculate the backreaction for this case and for a wide range of other two-fluid models. Here the effect is either suppressed because the nonideal matter properties are numerically too small, or because they lead to a too stringent UV cutoff of the integral over the power spectrum that determines backreaction. We discuss then matter field backreaction from a broader perspective and generalize the formalism such that also far-from-equilibrium scenarios relevant to late cosmological times and nonlinear scales can be addressed in the future.
Gesehen am 15.12.2021